2016
DOI: 10.7475/kjan.2016.28.4.378
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Fatigue and Distress on Self-efficacy among Breast Cancer Survivors

Abstract: Purpose:The purpose of this study was to describe the impact of fatigue and distress on self-efficacy among breast cancer survivors and to provide a base for development of nursing intervention strategy to improve self-efficacy. Methods: A descriptive research design was used. The subjects were 158 patients who were either being treated or were receiving follow-up care at a university breast center in D City from May 30 to August 30, 2014. Structured questionnaires, Revised Piper Fatigue Scale, Distress Thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…In addition, a previous study involving BCS reported a lower fatigue score (3.83) among subjects who were either undergoing active treatment or receiving follow-up care 27 ; however, that study's participants were an average of approximately 1 year post diagnosis, compared with 2.14 ± 1.77 years in our study. The observed differences in fatigue level may have been due to differences among studies in the number of participants in treatment as opposed to having completed treatment, but because cancer stage was not analyzed in 2 of the studies, 25,27 it is difficult to reach conclusions regarding the role of cancer stage. In addition, differences in the fatigue level could be related to survivorship phase (acute, extended, or permanent) 28 as well as to the cumulative effects of CRF over time.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…In addition, a previous study involving BCS reported a lower fatigue score (3.83) among subjects who were either undergoing active treatment or receiving follow-up care 27 ; however, that study's participants were an average of approximately 1 year post diagnosis, compared with 2.14 ± 1.77 years in our study. The observed differences in fatigue level may have been due to differences among studies in the number of participants in treatment as opposed to having completed treatment, but because cancer stage was not analyzed in 2 of the studies, 25,27 it is difficult to reach conclusions regarding the role of cancer stage. In addition, differences in the fatigue level could be related to survivorship phase (acute, extended, or permanent) 28 as well as to the cumulative effects of CRF over time.…”
Section: Discussioncontrasting
confidence: 84%
“…Another study of Korean BCS showed that patients undergoing RT had higher fatigue (5.04) than those receiving chemotherapy (4.03), but cancer stage was not significantly related to fatigue level 26 . In addition, a previous study involving BCS reported a lower fatigue score (3.83) among subjects who were either undergoing active treatment or receiving follow-up care 27 ; however, that study's participants were an average of approximately 1 year post diagnosis, compared with 2.14 ± 1.77 years in our study. The observed differences in fatigue level may have been due to differences among studies in the number of participants in treatment as opposed to having completed treatment, but because cancer stage was not analyzed in 2 of the studies, 25,27 it is difficult to reach conclusions regarding the role of cancer stage.…”
Section: Discussionmentioning
confidence: 97%
“…(2) Distress Thermometer (Korean Edition-NCCN Guidelines for Distress Management) Distress was measured using the Korean version of the national comprehensive cancer network (NCCN) distress thermometer (DT), [9] Korean Edition-NCCN Guidelines for Distress Management Version 2.2013. [10] The DT expresses the degree of distress felt in the past week, including the current day, on a rating scale from 0 (no distress) to 10 (excessive stress). The cutoff score is 4 points: mild distress < 4, moderate-to-severe distress ≥ 4.…”
Section: Patient Outcomesmentioning
confidence: 99%
“…(3) Inventory of Functional Status-Cancer (IFS-CA) Functional status was measured using the inventory of functional status-cancer (IFS-CA) developed by Tulman et al (1991) [9] and adapted to the Korean context by Seo and Lee (1997). [10] The IFS-CA is a 39-item questionnaire designed to measure the functional status of women with cancer, and consists of 4 subscales: household and family activities (15 items), social activities (6 items), self-care activities (10 items), and occupational activities (8 items). Each item is rated on a 4-point scale (1 = never, 4 = always).…”
Section: Patient Outcomesmentioning
confidence: 99%
See 1 more Smart Citation